If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(7x + 15) = 18 + 2c Reorder the terms: -2(15 + 7x) = 18 + 2c (15 * -2 + 7x * -2) = 18 + 2c (-30 + -14x) = 18 + 2c Solving -30 + -14x = 18 + 2c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + -14x = 18 + 30 + 2c Combine like terms: -30 + 30 = 0 0 + -14x = 18 + 30 + 2c -14x = 18 + 30 + 2c Combine like terms: 18 + 30 = 48 -14x = 48 + 2c Divide each side by '-14'. x = -3.428571429 + -0.1428571429c Simplifying x = -3.428571429 + -0.1428571429c
| 45=-15-6x | | 2(2x-4)+1=(3x-1)-2(x-3) | | 37=72-5y | | Sin(5x-28)=cos(3x-50) | | 54+72= | | 3(y+7)+2y=51 | | (x+5)(x-6)(x+13)=0 | | 7x+17=10x-10 | | 4.5x+3=4.2x+1.7 | | -7y-15=12 | | j/6=8 | | lnx=.85 | | x+7=14+2r | | 4x+8x-7= | | 4+5x-3+7+3(x-1)= | | 3[3a+2]=0 | | 7+3x=-6x+43 | | Ln(x)=-1.386 | | -6(u+1)=-8u-4 | | (3-8i)-(7-4i)=0 | | 7q+2q-p-5q= | | 60p^2+44p-56=0 | | 2(x+3)-(x-5)=x-5-3(x+2)+4x | | -x+4=7x+52 | | x=2.5y-13 | | 3t^2+17+24=0t | | 3(2x-6)=2(3x+9) | | 7x+6-5(-2x-1)=5(x-1) | | 4z=4.25+3.5 | | [(x*5)-12]*4=32 | | 3t^2+17+24=0 | | 2y+3.5-2=10 |